2010
DOI: 10.4049/jimmunol.0903109
|View full text |Cite
|
Sign up to set email alerts
|

Control of T Cell Reactivation by Regulatory Qa-1–Restricted CD8+ T Cells

Abstract: Administration of attenuated pathogenic T cell clones, a procedure known as T cell vaccination, induces CD8+ T cells specific for peptides derived from the Vβ-chain of the TCR presented by the MHC class Ib molecule, Qa-1 expressed on the vaccine cells. These regulatory CD8+ T cells have the capacity to control the activation of endogenous T cells expressing the same TCR Vβ-chain as the vaccinating cells. We hypothesized that vaccination with NKT cells could also induce Qa-1–restricted CD8+ T cells that would c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
(32 reference statements)
1
24
0
Order By: Relevance
“…As Qa-1 is the ligand of inhibitory receptor NKG2A, its downregulated expression on IECs may attenuate the inhibitory signal recognized by CD8 ϩ TCR␥␦ ϩ iIELs, leading to a reduction in the activation threshold of iIELs. In accordance with this, the human counterpart of Qa-1, HLA-E, was found to participate in a negative-feedback loop on cytotoxic T lymphocyte (CTL) responses in which TCR stimulation upregulates NKG2A expression and, in turn, NKG2A downregulates TCR activation by modifying antigen activation thresholds (12,13,27). The decreased expression of Ly49E and Ly49F on CD8 ϩ TCR␥␦ ϩ iIELs may also contribute to this effect.…”
Section: Discussionmentioning
confidence: 65%
“…As Qa-1 is the ligand of inhibitory receptor NKG2A, its downregulated expression on IECs may attenuate the inhibitory signal recognized by CD8 ϩ TCR␥␦ ϩ iIELs, leading to a reduction in the activation threshold of iIELs. In accordance with this, the human counterpart of Qa-1, HLA-E, was found to participate in a negative-feedback loop on cytotoxic T lymphocyte (CTL) responses in which TCR stimulation upregulates NKG2A expression and, in turn, NKG2A downregulates TCR activation by modifying antigen activation thresholds (12,13,27). The decreased expression of Ly49E and Ly49F on CD8 ϩ TCR␥␦ ϩ iIELs may also contribute to this effect.…”
Section: Discussionmentioning
confidence: 65%
“…[12][13][14][15][16] Previously unsuspected cell targets of CD8 + Tregs are Tfh cells because of their high basal expression of the Qa-1 molecule, 14 which is the mouse ortholog of the HLA-E molecule. The Qa-1 molecule can establish 2 types of molecular interactions: One with T cell receptors (TCRs) on CD8 + Tregs and the other with NKG2A receptors on CD8 + T cells and natural killer cells.…”
Section: Cd8mentioning
confidence: 99%
“…The same cells also reportedly induced CD4 1 T-cell anergy 5 and regulated reactivation of T and NKT cells. 6 Furthermore, antigen-induced CD8 1 CD103 1 Tregs have been shown to suppress effector T-cell function 7 and to be significantly increased in spontaneously tolerant recipients of liver allografts. 8 It has also been reported that Qa-1-restricted CD8 1 T cells regulate the activation of T cells as well as NKT cells.…”
Section: Introductionmentioning
confidence: 99%
“…8 It has also been reported that Qa-1-restricted CD8 1 T cells regulate the activation of T cells as well as NKT cells. 6 Therefore, CD8 1 CD28 2 , CD8 1 Qa-1 1 or CD8 1 CD103 1 Treg subsets may share the responsibility of maintaining immune homeostasis with other regulatory cell families, including CD4 1 CD25 1 FoxP3 1 and CD8 1 CD122 1 Tregs, although it remains to be defined whether and how the latter cells are associated with CD8 1 CD28 2 , CD8 1 CD103 1 or other CD8 1 Treg subsets. Understanding the relationship between CD8 1 CD122 1 and other subsets of CD8 1 Tregs through future studies may help in the design of new strategies to optimize their suppressive efficacy.…”
Section: Introductionmentioning
confidence: 99%